Experimental study on application characteristics of zeolite/water stuffing for the nanofluidic packer rubber. (November 2020) - Dou, Yihua; Zhang, Yafei; Liang, Jingwei; Chao, Rui
Aiming at sealing failure problem of packer rubber during well testing and completion, a new type of "nanofluidic packer rubber" is developed. The nanofluidic packer rubber is composed of honeycomb matrix skeleton encapsulating nanofluidic system as stuffing. Taking ZSM-5 zeolite/water nanofluidic system as an example stuffing for the nanofluidic packer rubber, the application properties are studied by means of experiment. Ten loading/unloading cycles are carried out on the pretreated zeolite/water stuffing at different loading rates and system temperatures on a pressure-volume characteristic test bench. The impact law of loading rate and system temperature on repeatable practicability, pressure threshold, and deformation capacity of the stuffing are obtained and the influence mechanisms are discussed. Results show that the zeolite/water stuffing works stable and repeatable after the first three loading/unloading cycles. The loading rate has lifting effects on throughput capacity, pressure threshold and deformation capacity when system temperature is under 75°C. With the increase of system temperature, pressure threshold decrease, and throughput capacity and deformation capacity increase. All the application characteristics found in zeolite/water stuffing are favorable for improving the working performance of packer rubber. This work provides theoretical and data support for the application of the nanofluidic packer rubber.